The Roots of Traditional Literature Interwoven in the Magical Universe of Harry Potter - Patiño Ramos, Stephanie (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The purpose of this paper is to highlight both, the validity and importance of traditional literature, in the creation of the diverse imaginary worlds offered by contemporary literature for young people. To this end, some of the topics and motifs of traditional literature, that weave the story of Harry Potter are analyzed. The focus is specifically on making an exhaustive comparative review on the appearance of the fatality of death, and the figure of "the unnamable" in traditional stories compiled by Wilhelm and Jacob Grimm and published in the first edition of Kinder- und Hausmärchen. By relating the stories of the Grimm brothers with some intradiegetic tales of the Harry Potter saga, it is evident how some stories are adapted from mythological tales and updated to a contemporary magical universe.